Juridical Implications of The Constitutional Court's Ruling for Impeachment of The President and/or Vice President if Proven to Have Committed Corruption - Agustono Agustono; Siti Rochmiyatun; Yazwardi Yazwardi (Syiar Hukum, 2022)
The assertion that the Indonesian state is based on law has proven that the law is placed at the most important level in the life of the state as a manifestation of the rule of law as commander in chief. Therefore, every attitude, decision, policy, behavior, act of state apparatus and citizens in the life of the nation and state must obey the applicable legal rules and norms, and this applies equally to every citizen so that they get equality before the law. The President and/or Vice President who carry out the mandate of the people as the Head of State and government, can be dismissed for reasons stipulated by the 1945 Constitution. The process of dismissing the President and/or Vice President from office has undergone various changes since the pre-amendment of the 1945 Constitution and Post-amendment, with its various characteristics, the 1945 Constitution has now provided space for the Constitutional Court to examine and adjudicate the opinion of the DPR in the context of dismissing the President and/or Vice President if it is suspected that they have committed unlawful acts or are no longer fit to serve as President. The 1945 Constitution also mandates that the process of dismissing the President and/or Vice President is taken through the parliamentary political process and then submitted to the legal process through the Constitutional Court, then returned to the political process at the MPR which determines the dismissal in the Plenary Session. Although the political process appears to be more dominantly put forward, so that constitutional debates arise in addressing the impeachment process in Indonesia, the crime responsibility of a President and/or Vice President must be processed thoroughly in accordance with the legal system in force in Indonesia, as a consequence of an act that violates the law.